2018
DOI: 10.1007/s10459-018-9814-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of postgraduate qualifications on educational identity formation of healthcare professionals

Abstract: Demand for postgraduate qualifications in medical education can be judged by the increase in providers worldwide over the last two decades. However, research into the impact of such courses on identity formation of healthcare professionals is limited. This study investigates the influence of such programmes on graduates' educational identities, practices and career progression. Informed by constructivist grounded theory (CGT), semistructured interviews were conducted with 27 graduates (2008-2012) from one post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 69 publications
4
60
0
Order By: Relevance
“…Byrne and Flood (2006) noted that while many accounting and business students pursue their degrees on the grounds that they are associated with job availability, financial return and job security, those students also demonstrate a lack of knowledge of what their future employment will actually involve. Finally, within health courses, many students assume that upon graduation they will be able to be employed in the profession for which the degree is named, sometimes ignorant of the fact that such employment can require postgraduate qualifications requiring competitive entry (Sethi, Schofield, McAleer, & Ajjawi, 2018). Collectively, this research reinforces the suggestion that many students may lack either clear expectations about, or accurate knowledge of the educationemployment pathways that lie before them.…”
Section: Literature Reviewsupporting
confidence: 60%
“…Byrne and Flood (2006) noted that while many accounting and business students pursue their degrees on the grounds that they are associated with job availability, financial return and job security, those students also demonstrate a lack of knowledge of what their future employment will actually involve. Finally, within health courses, many students assume that upon graduation they will be able to be employed in the profession for which the degree is named, sometimes ignorant of the fact that such employment can require postgraduate qualifications requiring competitive entry (Sethi, Schofield, McAleer, & Ajjawi, 2018). Collectively, this research reinforces the suggestion that many students may lack either clear expectations about, or accurate knowledge of the educationemployment pathways that lie before them.…”
Section: Literature Reviewsupporting
confidence: 60%
“…Additionally, HPE teachers may wish to consider pursuing formal teaching qualifications. Formal certification in this way has been shown to further promote legitimisation and professionalisation of the teaching role, encourage educational practice and scholarship, improve self-efficacy and foster belonging to an educator community (Sethi et al 2018).…”
Section: Suggestions For Teachersmentioning
confidence: 99%
“…It is surprising, then, that little has been published on the experiences and motivations of clinicians engaged in PGT programmes. Obtaining a Master’s degree is seen as desirable in healthcare education leaders (Tekian and Harris 2012) and such qualifications are often cited as essential in job specifications suggesting that graduates of such programmes go on to undertake influential roles (Steinert 2012; Sethi et al 2018). Sethi et al (2016) and Cunningham and Dovey (2016) surveyed graduates from medical education and general practice programmes respectively, indicating changes in practice, self-efficacy, critical thinking and sense of belonging to an academic community.…”
Section: Introductionmentioning
confidence: 99%
“…Sethi et al (2016) and Cunningham and Dovey (2016) surveyed graduates from medical education and general practice programmes respectively, indicating changes in practice, self-efficacy, critical thinking and sense of belonging to an academic community. Sethi et al (2018) reported that, independently of any gains in knowledge, the medical education postgraduate qualification itself was seen to aid career progression, indicating a potentially complex relationship between the benefits of what was learned on the programme and the status of the award.…”
Section: Introductionmentioning
confidence: 99%